Strategic value analysis of information technology investments - Arslan, Birgül. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2008., 2008)
This thesis seeks to shed light upon the strategic value of information technology (IT) investments. Previous literature suggests that IT investments per se are not sufficient for improving firm performance. Drawing from the resource-based view, it is hypothesized in this study that IT investments can deliver higher firm performance if they are (a) combined with complementary assets, (b) leveraged to build capabilities and (c) used to support organizational core competencies. Based on the data collected through a survey of thirty four companies, the findings show that IT support for core competencies has a significant positive effect on firm performance and the research model explains more than fifty percent variation of this performance. Furthermore, the relationship between IT infrastructure and IT-based capabilities as well as the relationship between IT-based capabilities and IT support for core competencies are found to be positive and significant. No support has been found for the business value of complementary assets. The study contributes to the literature by proposing a new measurement for IT infrastructure, improving the measurement for IT department human resources and including an extended set of other complementary resources. Furthermore, the study provides evidence from Turkey, a developing country.
Keywords: Management information systems.; Information technology -- Management.; Strategic planning.